Subgrade Optimization with Coconut Shell Ash Addition on Glee Gurah Clay Soil - Hidayat, Rifki; Azka, Cut Nawalul; Fatimah, Aldina; Firmansyah, Teuku Andrian (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Improving subgrade bearing capacity is a crucial aspect of highway construction. Clay soils, which have high plasticity and low bearing capacity, often require improvement to increase their stability and strength. This research examines the effect of coconut shell ash addition on the bearing capacity of clay soil in Glee Gurah village. The research aims to identify the impact of coconut shell ash stabilization on the mechanical characteristics of clay soil as a highway subgrade, focusing on soil compaction and CBR values. The research was conducted through a series of laboratory tests which included soil classification according to AASHTO and USCS, as well as compaction (Proctor) and CBR testing. The percentage variations of coconut shell ash used were 0%, 3%, 6%, 9%, and 12%. The results showed that the addition of coconut shell ash increased the bearing capacity of clay soil. The maximum dry volume weight increased from 1.464 gr/cm³ (no mixture) to 1.540 gr/cm³ at the addition of 12% coconut shell ash. The optimum moisture content decreased with increasing ash percentage, from 22.70% to 20.20%. The unsoaked CBR value also increased significantly, from 11.06% (no mixture) to 17.78% at the addition of 12% coconut shell ash, with a total CBR percentage increase of 60.80%. Thus, the use of 12% coconut shell ash > 20% (Good), so that ANOVA shows a p value <0.05, which means that the addition coconut shell ash significantly increases the bearing capacity of clay soil and is effective in strength of subgrades with moderate traffic categories. Key words: Stability, clay, Pavement, subgrade